Cellular SUMO-specific proteases regulate HAdV-C5 E1B-55K SUMOylation and virus-induced cell transformation - Ip, Wing-Hang; Fiedler, Marie; Gornott, Britta; Morische, Malte; Bertzbach, Luca D.; Dobner, Thomas (Frontiers in Cellular and Infection Microbiology, 2024)
Various viral proteins are post-translationally modified by SUMO-conjugation during the human adenovirus (HAdV) replication cycle. This modification leads to diverse consequences for target proteins as it influences their intracellular localization or cell transformation capabilities. SUMOylated HAdV proteins include the multifunctional oncoprotein E1B-55K. Our previous research, along with that of others, has demonstrated a substantial influence of yet another adenoviral oncoprotein, E4orf6, on E1B-55K SUMOylation levels. Protein SUMOylation can be reversed by cellular sentrin/SUMO-specific proteases (SENPs). In this study, we investigated the interaction of E1B-55K with cellular SENPs to understand deSUMOylation activities and their consequences for cell transformation mediated by this adenoviral oncoprotein. We show that E1B-55K interacts with and is deSUMOylated by SENP 1, independently of E4orf6. Consistent with these results, we found that SENP 1 prevents E1A/E1B-dependent focus formation in rodent cells. We anticipate these findings to be the groundwork for future studies on adenovirus-host interactions, the mechanisms that underlie E1B-55K SUMOylation, as well as the role of this major adenoviral oncoprotein in HAdV-mediated cell transformation.